Group B Streptococcus impairs erythrocyte deformability in neonates more than in adults. Issue 3 (May 1996) - Pöschl, J. M.; Ruef, P.; Schnauffer, M.; Pohl, S.; Sonntag, H. G.; Linderkamp, O.
Abstract : Group B beta-haemolytic Streptococcus (GBS) may cause severe septic shock and death in neonates, whereas this is rarely the case in adults. As impaired red blood cell (RBC) deformability might disturb microcirculation in septic shock, the in vitro effects of GBS (1.7 x 10(8) cfu/ml) on RBC deformation (rheoscope) and haemolysis were studied in blood from preterm infants, term neonates, and adults. Furthermore, RBC deformation was studied in term neonates with GBS sepsis. RBC deformation at a shear stress of 4 Pa decreased significantly within 5 minutes of GBS incubation in preterm infants (-13%) and term neonates (-9%). In adults RBC deformation did not change during the first 15 minutes, but decreased significantly after 30 (-10%) and 60 minutes (-13%). In the term infants there was little further decrease in RBC deformation between 5 and 60 minutes of GBS incubation; RBC deformation in preterm infants decreased by 19% after 60 minutes compared with the preincubation values. RBC deformation in septic neonates was significantly decreased at shear stresses of 1, 2, and 3 Pa (-19%, -18%, and -9%). Sixty minutes of incubation of RBC from adults and neonates with GBS and without GBS resulted in haemolysis below 4%. It is concluded that neither neonatal nor adult RBC are haemolysed by GBS. In vitro, neonatal RBC deformability is more impaired than that in adults. This may contribute to the high risk of neonates for compromised microcirculation and circulatory shock as a result of GBS sepsis.